Dante - Took, J. F. (Princeton University Press, 2020)
An authoritative and comprehensive intellectual biography of the author of the Divine Comedy. For all that has been written about the author of the Divine Comedy, Dante Alighieri (1265-1321) remains the best guide to his own life and work. Dante's writings are therefore never far away in this authoritative and comprehensive intellectual biography, which offers a fresh account of the medieval Florentine poet's life and thought before and after his exile in 1302. Beginning with the often violent circumstances of Dante's life, the book examines his successive works as testimony to the course of his passionate humanity: his lyric poetry through to the Vita nova as the great work of his first period; the Convivio, De vulgari eloquentia and the poems of his early years in exile; and the Monarchia and the Commedia as the product of his maturity. Describing as it does a journey of the mind, the book confirms the nature of Dante's undertaking as an exploration of what he himself speaks of as "maturity in the flame of love." The result is an original synthesis of Dante's life and work